Tværfagligt samarbejde, forskning, formidling og vores fælles fremtid inden for bygningsrestaurering - Bjarnhof, Rikke (Hikuin, 2011)
The preservation of historic interiors is carried out in collaboration between many related professions. The best solutions of combining historical context with modern function in the preservation of buildings and their contents are achieved through multidisciplinarity. Respect for professional recommendations and mutual understanding can improve collaboration and optimize decision making. The field of buildings-related conservation is constantly under development. Advances include new technology, methods of analysis, research and advances in treatment methodology. Sharing of new scientific results and empirical knowledge with colleagues, partners, and the new generation of students within building preservation is of greatest importance to promote, implement, and maintain high standards.Creating multidisciplinary networking can develop the mutual understanding necessary to achieve these goals. An accessible data bank including relevant information about particular buildings would be an advantage for all participants caring for our common cultural heritage, giving a broader, more qualified and better basis for decision making.